ʿAqd al-Nikāḥ: Explaining the Nexus Between Marriage and Contract in Islamic Law - Hakime Reyyan Yaşar (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
The combination of marriage and contract (ʿaqd al-nikāḥ) has been one of the interesting subjects for the scholars to be discuss and elaborate. The focus of this attention has been on analysis and understanding of the contractual component of the marriage reflecting a similarity with economic contracts. Recent studies endeavored to explain this nexus; however, they have also neglected to include how contract as a concept operates in Islamic law and beyond, and the discussions between the schools on the metaphoric aspect of the marriage contract. Classical legal scholars elaborated how marriage is represented by contract model, its relation to other economic contracts, and how the contractual aspect of the marriage is articulated. In particular, the argument that the contractual aspect of nikāḥ is partly related to metaphor offers another dimension in exploring the nature of the marriage contract. This study aims to analyse the nexus by including both the discussions on the metaphoric aspect of the marriage contract and the shortcomings in explanations of the contractual component of the marriage contract.